2021
DOI: 10.1038/s41598-021-02078-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ROX and HACOR scales to predict high-flow nasal cannula failure in patients with SARS-CoV-2 pneumonia

Abstract: The pandemic of SARSCov2 infection has created a challenge in health services worldwide. Some scales have been applied to evaluate the risk of intubation, such as the ROX and HACOR. The objective of this study is to compare the predictive capacity of the HACOR scale and the ROX index and define the optimal cut-off points. Study of diagnostic tests based on a retrospective cohort. Composite outcome was the proportion of patients that needed endotracheal intubation (ETI) or died of COVID19 pneumonia. Discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
0
14
1
2
Order By: Relevance
“…Second, regarding the utility of the ROX index, the authors contradicted the results of a recent meta-analysis ( 2 ). For Burnim et al ( 1 ), this index performed poorly, as recently reported in another cohort ( 3 ). The authors performed an additional model including “demographic, clinical, and laboratory variables” and found a better predictor of IMV.…”
Section: To the Editormentioning
confidence: 56%
“…Second, regarding the utility of the ROX index, the authors contradicted the results of a recent meta-analysis ( 2 ). For Burnim et al ( 1 ), this index performed poorly, as recently reported in another cohort ( 3 ). The authors performed an additional model including “demographic, clinical, and laboratory variables” and found a better predictor of IMV.…”
Section: To the Editormentioning
confidence: 56%
“…In 128 hypoxemic patients with COVID-19 undergoing CPAP, Guia et al observed that a HACOR score > 5 was associated with an increased risk of CPAP failure [ 11 ], defined as the need for intubation or death. In a retrospective cohort of patients with COVID-19-related pneumonia undergoing respiratory support with high flow nasal cannula, Valencia et al [ 12 ] found that the HACOR score predicted the need for intubation or death, with an optimal cut-off point of 5.5 [ 12 ]. As in previous studies, we found an association between a high 1-h HACOR score (i.e., >5) and the occurrence of either need for intubation or in-hospital death, after adjustment for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of the HACOR score (measured 1 h after NIRS initiation) in patients with COVID 19-related ARF, has been investigated by Guia et al [ 11 ]; they observed a good performance of a HACOR score > 5 in predicting Continue Positive Airway Pressure (CPAP) failure, defined as the need for orotracheal intubation or death in COVID-19-related ARF [ 11 ]. Valencia et al [ 12 ] found a moderate capacity of the HACOR score to predict the failure (i.e., need for mechanical ventilation and death) of high flow nasal cannula treatment in patients with COVID-19 pneumonia. Whether an early determination of the HACOR score (i.e., calculated before the initiation of NIRS treatment) might be useful for predicting unfavorable in-hospital prognosis, has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, comorbidities such as hypertension and chronic kidney disease as well as bacterial co-infections may predict worse treatment outcomes 68 .…”
Section: Poor Prognosis Scoresmentioning
confidence: 99%